Analysis of Management Responses of RSI Kendal to Deal with the Covid-19 Pandemic in 2021 - Antono Suryoputro; Martini Martini; Mulyati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: The high number of positive cases of Covid-19 in Indonesia has made the Government of Indonesia stipulate it as a national non-natural disaster. Various obstacles related to hospital services emerged due to a significant increase in patients at the same time. Given these constraints, there needs to be a hospital management response to maintain health services at the hospital to continue to run well. Objective: The purpose of this study is to get an overview of the response of hospital management in dealing with the Covid-19 pandemic in 2021 through the rapid hospital readiness for Covid-19 instrument recommended by WHO. Methods: This research is a qualitative research with a phenomenological approach. Data collection was carried out through interviews with five main informants and 17 triangulation informants, as well as through observation. Results: showed that from the assessment of the 12 components of rapid hospital readiness for covid-19, it was found that components could not be implemented optimally, namely leadership and incident management systems (86%), administrative, financial and business continuity (87%), patient management (88%) ), proper identification and diagnosis (83%), PPI (94%) and the lowest is occupational health, mental health and psychosocial support (40%). Conclution: The management response of Kendal Hospital in dealing with the 2021 Covid-19 pandemic has been good, the lack of implementation of the rapid hospital readiness instrument for Covid-19 is technical.